Fine aggregate reinforced fluidified solidified soil composition, fine aggregate reinforced fluidified solidified soil, and preparation method and application thereof

CN122878102APending Publication Date: 2026-10-09NAT ENG LAB FOR HIGH SPEED RAILWAY CONSTR +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611400736.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]但是,现有技术往往无法兼顾流态固化土的抗压强度、抗折性能、水稳定性和重金属浸出控制;如CN120349139A公开了一种固废基流态固化土及其制备方法,该方案难以从浆体体系内部提升材料均匀性、抗分层稳定性、界面过渡区质量和整体抗折韧性;如CN121873812A公开了一种用于流态固化土的多元固废基土壤固化剂,但未整体考虑其制备得到的流态固化土在实际应用中的流动性、泌水率、分层度、抗折强度和水稳定性等性能指标,同时,该方案提供的添加剂仅涉及吸附和保水,未形成重金属固化、成膜增韧、抗分层调黏及憎水抗水损的协同功能体系

Benefits of technology

(1)本发明通过工程渣土、胶凝组分、细骨料、超细填料、重金属固化剂、成膜增韧剂、抗分层黏度调节剂、助剂等组分的协同作用,使其制得的流态固化土具有优异的流动性、低的分层度、高的抗压强度和抗折强度、优异的浸水后强度保持率以及重金属固化率等性能,适用于对均匀性、耐久性和环境安全性要求较高的工程场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The present application relates to the technical field of flow state solidified material and contaminated soil remediation material, and discloses a fine aggregate reinforced flow state solidified soil composition, a fine aggregate reinforced flow state solidified soil, and a preparation method and application thereof.The composition contains engineering spoil, cementing components, fine aggregate, superfine filler, heavy metal solidifying agent, film-forming toughening agent, anti-delamination viscosity regulator, auxiliary agent and water.The fine aggregate is continuously graded quartz sand.The superfine filler contains limestone and silica fume.The heavy metal solidifying agent contains sodium alginate and carboxymethyl chitosan in a mass ratio of 1:0.25-3.The film-forming toughening agent contains vinyl acetate-ethylene copolymer latex powder and butadiene-styrene latex in a mass ratio of 1:0.5-0.8.The flow state solidified soil provided by the present application has good anti-delamination, water stability, mechanical strength and heavy metal leaching control ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fluidized bed materials and contaminated soil remediation materials, specifically to a composition for fine aggregate reinforced fluidized bed soil, fine aggregate reinforced fluidized bed soil, its preparation method and application. Background Technology

[0002] Fluidized solidified soil has been widely used in trench backfilling, underground cavity filling, road repair, micro-disturbance reinforcement of existing structures, and soft foundation treatment due to its advantages such as self-leveling, self-compacting, minimal construction disturbance, and suitability for filling narrow and irregular spaces.

[0003] In practical engineering applications, to improve the later-stage strength of fluidized solidified soil, reduce its shrinkage deformation, and lower material costs, existing research mainly involves adding a certain amount of fine aggregate, or even a small amount of small-diameter aggregate, to the fluidized solidified soil. However, fine aggregate (especially fine aggregate with large particle size and discontinuous gradation) easily leads to pulp-aggregate separation, bleeding, sedimentation, or stratification, ultimately causing problems such as unevenness of the fluidized solidified soil body, insufficient local strength, and poor water stability. Although some systems improve the early-stage strength of fluidized solidified soil by increasing the amount of cementitious materials, they suffer from high costs, high brittleness, significant performance degradation after immersion in water, and easy stratification even after adding aggregate. In addition, simply increasing the amount of water to improve the fluidity of fluidized solidified soil can easily further aggravate bleeding and aggregate settling. However, relying on water-reducing agents to improve fluidity often leads to insufficient cohesion of the system.

[0004] On the other hand, in applications such as contaminated site remediation, industrial site backfilling, and resource utilization of dredged sediment, fluidized solidified soil also needs to have good heavy metal solidification capabilities to reduce the leaching risk of heavy metals such as lead, cadmium, chromium, copper, and zinc.

[0005] However, existing technologies often fail to simultaneously address the compressive strength, flexural strength, water stability, and heavy metal leaching control of fluidized solidified soil. For example, CN120349139A discloses a solid waste-based fluidized solidified soil and its preparation method, but this approach struggles to improve material uniformity, anti-stratification stability, interfacial transition zone quality, and overall flexural toughness from within the slurry system. Similarly, CN121873812A discloses a multi-element solid waste-based soil stabilizer for fluidized solidified soil, but it does not comprehensively consider the fluidity, bleeding rate, stratification degree, flexural strength, and water stability of the prepared fluidized solidified soil in practical applications. Furthermore, the additives provided in this approach only involve adsorption and water retention, failing to form a synergistic functional system encompassing heavy metal solidification, film-forming toughening, anti-stratification viscosity adjustment, and hydrophobic resistance to water loss.

[0006] Therefore, there is an urgent need to provide a fluidized solidified soil that, after the addition of fine aggregate, ensures fluidized construction performance while maintaining excellent uniformity and anti-segregation properties, and also possesses heavy metal solidification, flexural strength, compressive strength, and water stability, thus making it suitable for more complex engineering applications. Summary of the Invention

[0007] The purpose of this invention is to provide a fluidized solidified soil that, when fine aggregate is added, can simultaneously achieve good mechanical properties, anti-segregation, water stability, and heavy metal leaching control.

[0008] To achieve the above objectives, a first aspect of the present invention provides a composition for fine aggregate reinforced fluidized solidified soil, the composition comprising engineering waste soil, cementitious components, fine aggregate, ultrafine filler, heavy metal curing agent, film-forming toughening agent, anti-segregation viscosity regulator, additives and water; Relative to 100 parts by weight of the engineering waste soil, the content of the cementitious component is 15-45 parts by weight, the content of the fine aggregate is 10-60 parts by weight, the content of the ultrafine filler is 4-20 parts by weight, the content of the heavy metal curing agent is 0.2-2.5 parts by weight, the content of the film-forming toughening agent is 1-8 parts by weight, the content of the anti-delamination viscosity modifier is 0.01-0.2 parts by weight; the content of the additives is 0.21-3.3 parts by weight, and the content of water is 25-50 parts by weight. Based on the total mass of the cementitious components, the cementitious components contain 25-45 wt% sulfoaluminate cement, 20-35 wt% silicate cement, 10-30 wt% slag powder, 5-20 wt% fly ash and 2-10 wt% gypsum. The fine aggregate is continuously graded quartz sand, and the particle size of the quartz sand is not greater than 4.75 mm. The ultrafine filler contains limestone and silica fume; and the median particle size D of the ultrafine filler is... 50 The range is 0.05-20 μm; The heavy metal curing agent contains sodium alginate and carboxymethyl chitosan in a mass ratio of 1:0.25-3; The film-forming toughening agent contains vinyl acetate-ethylene copolymer latex powder and styrene-butadiene latex in a mass ratio of 1:0.5-0.8.

[0009] A second aspect of the present invention provides a method for preparing fine aggregate reinforced fluidized solidified soil, the method comprising using the components of the composition described in the first aspect, including: S1: The engineering waste soil, cementing components, ultrafine fillers, heavy metal curing agents and vinyl acetate-ethylene copolymer latex powder are mixed in the first step to obtain mixture I; S2: The anti-stratification viscosity modifier, water-reducing agent, defoamer and water are mixed for the second time to obtain mixture II; S3: Contact the mixture I with the mixture II and fine aggregate to obtain intermediate material; S4: The intermediate material, styrene-butadiene latex and hydrophobic component are mixed in a third mixture to obtain mixture III; S5: The mixture III is poured and molded sequentially to obtain the fluidized solidified soil.

[0010] A third aspect of the present invention provides a fine aggregate reinforced fluidized solidified soil prepared by the method described in the second aspect.

[0011] The fourth aspect of the present invention provides the application of the fine aggregate reinforced fluidized solidified soil described in the third aspect in backfilling contaminated sites, filling underground cavities, backfilling trenches, remediation of subsidence, filling voids in underwater environments or under high groundwater conditions, and low-disturbance grouting repair of existing facilities.

[0012] Compared with the prior art, the present invention has at least the following advantages: (1) Through the synergistic effect of components such as engineering slag, cementing components, fine aggregates, ultrafine fillers, heavy metal curing agents, film-forming toughening agents, anti-segregation viscosity regulators, and additives, the present invention produces fluidized solidified soil with excellent fluidity, low segregation, high compressive strength and flexural strength, excellent strength retention rate after immersion in water, and high heavy metal curing rate, which is suitable for engineering scenarios with high requirements for uniformity, durability and environmental safety.

[0013] (2) By using fine aggregates with continuous gradation characteristics in combination with ultrafine fillers containing limestone and silica fume, the present invention significantly improves the ability of fluidized solidified soil slurry to encapsulate aggregates and its suspension stability, thereby avoiding obvious stratification, bleeding and settling caused by the incorporation of fine aggregates.

[0014] (3) By introducing a heavy metal curing agent containing sodium alginate and carboxymethyl chitosan in a mass ratio of 1:0.25-3, this invention can work together with the hydration products of cement and mineral admixtures to achieve synergistic curing of heavy metal ions through complexation, adsorption, encapsulation and precipitation, thereby effectively reducing the concentration of heavy metal leaching.

[0015] (4) By introducing a film-forming toughening agent containing vinyl acetate-ethylene copolymer latex powder and styrene-butadiene latex, the present invention can form a flexible polymer film, thereby improving the interfacial transition zone inside the fluidized solidified soil, enhancing its flexural strength and crack resistance, and improving its toughness to a certain extent. Detailed Implementation

[0016] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0017] In this invention, particle size refers to the diameter of the particle.

[0018] In this invention, continuous gradation refers to mixing quartz sand particles of different sizes in a certain proportion so that quartz sand particles exist in each size grade from the smallest to the largest particle size, and there are no obvious breaks or gaps in between.

[0019] In this invention, the surface dry saturation state refers to the state in which the internal pores of the fine aggregate are basically saturated with water, and there is basically no visible free water or open water on the surface of the fine aggregate particles.

[0020] As previously mentioned, a first aspect of the present invention provides a composition for fine aggregate reinforced fluidized solidified soil, the composition comprising engineering waste soil, cementitious components, fine aggregate, ultrafine filler, heavy metal curing agent, film-forming toughening agent, anti-segregation viscosity modifier, additives and water; Relative to 100 parts by weight of the engineering waste soil, the content of the cementitious component is 15-45 parts by weight, the content of the fine aggregate is 10-60 parts by weight, the content of the ultrafine filler is 4-20 parts by weight, the content of the heavy metal curing agent is 0.2-2.5 parts by weight, the content of the film-forming toughening agent is 1-8 parts by weight, the content of the anti-delamination viscosity modifier is 0.01-0.2 parts by weight; the content of the additives is 0.21-3.3 parts by weight, and the content of water is 25-50 parts by weight. Based on the total mass of the cementitious components, the cementitious components contain 25-45 wt% sulfoaluminate cement, 20-35 wt% silicate cement, 10-30 wt% slag powder, 5-20 wt% fly ash and 2-10 wt% gypsum. The fine aggregate is continuously graded quartz sand, and the particle size of the quartz sand is not greater than 4.75 mm. The ultrafine filler contains limestone and silica fume; and the median particle size D of the ultrafine filler is... 50 The range is 0.05-20 μm; The heavy metal curing agent contains sodium alginate and carboxymethyl chitosan in a mass ratio of 1:0.25-3; The film-forming toughening agent contains vinyl acetate-ethylene copolymer latex powder and styrene-butadiene latex in a mass ratio of 1:0.5-0.8.

[0021] More preferably, relative to 100 parts by weight of the engineering waste soil, the content of the cementitious component is 20-38 parts by weight, the content of the fine aggregate is 20-50 parts by weight, the content of the ultrafine filler is 10-15 parts by weight, the content of the heavy metal solidifying agent is 0.5-1.5 parts by weight, the content of the film-forming toughening agent is 2-6 parts by weight, the content of the anti-segregation viscosity modifier is 0.03-0.12 parts by weight, the content of the additives is 0.4-3 parts by weight, and the content of water is 30-50 parts by weight. Under these preferred conditions, the prepared fluidized solidified soil can better balance mechanical properties, anti-segregation stability, water stability, and heavy metal leaching inhibition ability.

[0022] Preferably, the median grain size D of the limestone is... 50 It is 3-10μm.

[0023] Preferably, the median particle size D of the silica fume is... 50 It is 0.1-0.5μm.

[0024] It should be noted that in the fine aggregate reinforced fluidized solidified soil composition provided by the present invention, the content of the engineering waste soil is based on its oven-dry weight, which refers to the constant weight reached by the engineering waste soil after drying at (105±2)℃ for 24 hours; the content of the film-forming toughening agent is based on the effective polymer solids content therein, that is, the sum of the solids of vinyl acetate-ethylene copolymer latex powder on a dry basis and the dry basis solids of styrene-butadiene latex calculated according to solid content; the water does not include water that may be contained in the other components of the composition.

[0025] In this invention, among the cementitious components, the sulfoaluminate cement can promote the rapid generation of early hydration products such as ettringite, thereby realizing the construction of the early microstructure of the fluidized solidified soil; the silicate cement can provide later strength growth through continuous hydration reaction, thereby ensuring the long-term mechanical properties of the prepared fluidized solidified soil; the slag powder and fly ash can improve the later compaction and heavy metal fixation capacity of the fluidized solidified soil; and the gypsum can regulate the hydration reaction and participate in the early structural formation of the fluidized solidified soil.

[0026] In this invention, a heavy metal curing agent containing sodium alginate and carboxymethyl chitosan in a mass ratio of 1:0.25-3 exhibits a better heavy metal leaching inhibition rate. This is because the carboxyl groups in sodium alginate can form coordination or ionic crosslinks with polyvalent metal ions, while the amino and carboxyl groups in carboxymethyl chitosan can adsorb and complex heavy metal ions. Both can synergistically interact with the hydration products in the gelation system, thereby improving the heavy metal fixation effect. The mass ratio of sodium alginate to carboxymethyl chitosan can be any one or a range of two of the following: 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.5, 1:2, 1:2.5, 1:3; preferably 1:0.25-1.

[0027] In this invention, a film-forming toughening agent composed of vinyl acetate-ethylene copolymer latex powder and styrene-butadiene latex in a mass ratio of 1:0.5-0.8 can further improve the density and adhesion continuity of the interfacial transition zone by forming a polymer network, and improve the flexural strength and water loss resistance of the fluidized solidified soil.

[0028] Preferably, based on the total mass of the fine aggregate, the content of quartz sand with a particle size greater than or equal to 0.075 mm and less than 0.6 mm is 40-80 wt%, the content of quartz sand with a particle size greater than or equal to 0.6 mm and less than or equal to 1.18 mm is 20-60 wt%, and the content of quartz sand with a particle size greater than 1.18 mm and less than or equal to 4.75 mm is 0-25 wt%. In this preferred embodiment, the smaller particle size of the quartz sand can fill the pores between the larger particle size of the quartz sand, forming a dense packing structure, reducing the overall porosity of the fine aggregate system, further reducing the amount of free water required for the slurry to fill the pores of the aggregate, and further improving the continuity of the slurry's encapsulation of the quartz sand particles and the suspension stability. The resulting fluidized solidified soil has better construction performance, lower risk of stratification and sedimentation, and the solidified body has higher compressive strength, flexural strength, and water stability.

[0029] Preferably, based on the total mass of the cementitious components, the cementitious components contain 30-40 wt% sulfoaluminate cement, 20-30 wt% silicate cement, 20-25 wt% slag powder, 8-15 wt% fly ash, and 4-8 wt% gypsum. Under this preferred condition, the components in the prepared fluidized solidified soil exhibit better synergistic hydration, enabling faster formation of the early structure and sustained development of later strength in the fluidized solidified soil. It also possesses a superior solidified pore structure and better compactness, further improving its early forming stability, compressive strength, flexural strength, strength retention rate after immersion in water, and heavy metal leaching inhibition ability.

[0030] Preferably, the anti-stratification viscosity modifier contains vestigma and hydroxypropyl methylcellulose in a mass ratio of 1:0.5-1.0.

[0031] More preferably, the anti-segregation viscosity modifier contains vesylvaline and hydroxypropyl methylcellulose in a mass ratio of 1:0.5-0.7. Under this preferred condition, the prepared fluidized solidified soil has higher water stability, stronger water retention and cohesiveness, and can better suppress the segregation of fine aggregates while taking into account the fluidity of the system.

[0032] More preferably, the content of the anti-stratification viscosity modifier is 0.03-0.12 parts by weight.

[0033] Preferably, the content of the film-forming toughening agent is 2-5 parts by weight.

[0034] Preferably, the engineering waste soil is selected from at least one of engineering waste soil and dehydrated soil from engineering waste soil, and the particle size of the engineering waste soil is not greater than 4.75 mm. The excavated soil for the project is selected from at least one of silty clay, silty soil, and dredged bottom mud.

[0035] More preferably, based on the total mass of the engineering waste soil, it contains 40-70 wt% SiO2 and 5-30 wt% Al2O3. In addition to SiO2 and Al2O3, the engineering waste soil described in this invention also contains impurities and water.

[0036] The impurities in the engineering waste soil mentioned in this invention refer to substances other than SiO2, Al2O3, and water, including plant root impurities, engineering residues, etc.

[0037] In some embodiments, the particle size of the engineering waste soil can be, for example, 0.75mm, 1.25mm, 1.75mm, 2.25mm, 2.75mm, 3.25mm, 3.75mm, 4.25mm, or 4.75mm. In this embodiment, the uniformity of dispersion of the engineering waste soil in the slurry and the contact reaction area with the cementitious components are further improved, and the risks of settlement, segregation, and localized uneven strength caused by large soil particles in the fluidized solidified soil are further reduced.

[0038] Preferably, in the ultrafine filler, the mass ratio of limestone to silica fume is 3-10:1. In this preferred embodiment, the ultrafine filler can fill the pores of the fluidized solidified soil and improve its cohesiveness, thereby enhancing the encapsulation effect on the fine aggregate and improving its suspension capacity.

[0039] Preferably, relative to 100 parts by weight of the engineering waste soil, the additive contains 0.1-2.0 parts by weight of a hydrophobic component, 0.1-1.2 parts by weight of a water-reducing agent, and 0.01-0.1 parts by weight of a defoamer.

[0040] More preferably, the hydrophobic component is a siloxane emulsion.

[0041] In some embodiments, the siloxane emulsion includes siloxane emulsions and / or silane emulsions capable of hydrolysis and condensation in an aqueous system to generate siloxanes.

[0042] According to a particularly preferred embodiment of the present invention, the hydrophobic component is a siloxane emulsion; in this preferred case, the strength retention rate and impermeability of the fluidized solidified soil containing the hydrophobic component after immersion can be further improved.

[0043] More preferably, the water-reducing agent is selected from at least one of polycarboxylate water-reducing agents, naphthalene-based water-reducing agents, and aminosulfonate-based water-reducing agents.

[0044] According to a particularly preferred embodiment of the present invention, the water-reducing agent is a polycarboxylate water-reducing agent.

[0045] In some embodiments, the defoamer is selected from at least one of silicone defoamers, polyether defoamers, and mineral oil defoamers.

[0046] According to a particularly preferred embodiment of the present invention, the defoamer is an organosilicon defoamer.

[0047] As previously described, a second aspect of the present invention provides a method for preparing fine aggregate-reinforced fluidized solidified soil, the method comprising using the components of the composition described in the first aspect, including: S1: The engineering waste soil, cementing components, ultrafine fillers, heavy metal curing agents and vinyl acetate-ethylene copolymer latex powder are mixed in the first step to obtain mixture I; S2: The anti-stratification viscosity modifier, water-reducing agent, defoamer and water are mixed for the second time to obtain mixture II; S3: Contact the mixture I with the mixture II and fine aggregate to obtain intermediate material; S4: The intermediate material, styrene-butadiene latex and hydrophobic component are mixed in a third mixture to obtain mixture III; S5: The mixture III is poured and molded sequentially to obtain the fluidized solidified soil.

[0048] It should be noted that the present invention does not impose special requirements on the specific operation methods and conditions of the first mixing and the second mixing, as long as the materials are mixed evenly. Those skilled in the art can use conventional methods, and the present invention does not limit these methods and should not be construed as limiting the present invention. For example, the conditions for the first mixing include mixing at 100-300 rpm for 1-2 minutes; the conditions for the second mixing include mixing at 300-800 rpm for 0.5-1.5 minutes.

[0049] In some embodiments, step S3 further includes: pre-wetting the fine aggregate to a surface-dry saturated state, and then contacting mixture I with mixture II and the fine aggregate to obtain an intermediate material. It should be noted that the present invention uses water to pre-wet the fine aggregate to a surface-dry saturated state; the amount of water used here is not included in the water content of the composition described in the first aspect of the present invention. This step is merely a raw material pretreatment process and should not be construed as a limitation of the present invention. In this embodiment, the fluidized solidified soil prepared by this method has a more stable actual water-cement ratio and better slurry rheological properties.

[0050] Preferably, in step S3, the specific operation of the contact includes: Mixture I and mixture II are brought into a first contact to obtain the material after the first contact. This material is then brought into a second contact with the fine aggregate to obtain the intermediate material. In this preferred embodiment, the material after the first contact has better cohesiveness, thereby better preventing the fine aggregate from rapidly settling in the initial low-viscosity stage; the fine aggregate can be more fully coated by the cementitious components and ultrafine fillers, thus forming a more stable coating system, thereby improving the uniformity of the prepared fluidized solidified soil.

[0051] Preferably, the first contact and the second contact are carried out under stirring conditions.

[0052] More preferably, the conditions for the first contact include: stirring at 150-300 rpm for 0.5-1.5 min, then stirring at 600-1000 rpm for 1.5-3 min and letting stand for 1-3 min.

[0053] More preferably, the specific operation of the second contact includes: dividing the fine aggregate into 2-3 equal parts according to the total mass, and adding the fine aggregate to the material after the first contact in batches at 300-600 rpm; the stirring time for each batch is 30-90 s.

[0054] Preferably, the total time for the first and second contact is 4.5-7.5 min.

[0055] In some embodiments, the third mixing conditions in step S4 include stirring at 300-600 rpm for 0.5-2 min. In this embodiment, the incorporation of a hydrophobic component in step S4 facilitates the formation of a hydrophobic interface in mixture III, thereby improving the strength retention rate of the fluidized solidified soil after immersion in water.

[0056] In some embodiments, step S4 further includes allowing the third mixed material to stand for 1-3 minutes to obtain mixture III. In this embodiment, the prepared fluidized solidified soil slurry has better uniformity and construction fluidity, thereby making the performance of the prepared fluidized solidified soil more stable.

[0057] In some embodiments, step S5 further includes: stirring the mixture III for 0.5-1.0 min before pouring, and then pouring, molding and curing in sequence to obtain the fluidized solidified soil.

[0058] The present invention does not have any special requirements for the pouring, molding and curing methods. Those skilled in the art can carry out the pouring, molding and curing of the fluidized solidified soil slurry in sequence, according to the known technical means in the field. For example, the pouring, molding and curing of the fluidized solidified soil slurry can be carried out in accordance with DBJ51-T188-2022 "Technical Standard for Engineering Application of Premixed Fluidized Solidified Soil".

[0059] As previously stated, a third aspect of the present invention provides a fine aggregate reinforced fluidized solidified soil prepared by the method described in the second aspect.

[0060] As previously stated, the fourth aspect of the present invention provides the application of the fine aggregate reinforced fluidized solidified soil described in the third aspect in backfilling contaminated sites, filling underground cavities, backfilling trenches, remediation of subsidence, filling voids in underwater environments or under high groundwater conditions, and low-disturbance grouting repair of existing facilities.

[0061] The present invention will be described in detail below through embodiments. In the following embodiments, unless otherwise specified, all raw materials are commercially available products: Construction waste soil: The type is construction waste soil from a construction site in Changsha City. After drying, crushing and screening, its maximum particle size is no more than 4.75mm. The content of SiO2 is 63.72wt%, the content of Al2O3 is 15.59wt%, and the balance is water and impurities; the initial moisture content is 18.9wt%.

[0062] Sulfoaluminate cement: Grade 52.5 rapid-hardening sulfoaluminate cement, purchased from Tangshan Arctic Bear Building Materials Co., Ltd.

[0063] Portland cement: PO 42.5 ordinary Portland cement, purchased from Anhui Conch Cement Co., Ltd.

[0064] Slag powder: Grade S95 granulated blast furnace slag powder, purchased from Baowu Group Environmental Resources Technology Co., Ltd.

[0065] Fly ash: Grade II fly ash, purchased from Zhucheng Jiuqi Building Materials Co., Ltd.

[0066] Gypsum: Model is building gypsum, purchased from Zhucheng Jiuqi Building Materials Co., Ltd.

[0067] Cementitious Component I: Based on the total mass of cementitious components, the content of sulfoaluminate cement is 35.71 wt%, silicate cement is 25 wt%, slag powder is 21.43 wt%, fly ash is 10.71 wt%, and gypsum is 7.15 wt%.

[0068] Cementitious Component II: Based on the total mass of cementitious components, the content of sulfoaluminate cement is 34.37 wt%, silicate cement is 25 wt%, slag powder is 21.88 wt%, fly ash is 12.5 wt%, and gypsum is 6.25 wt%.

[0069] Cementitious Component III: Based on the total mass of cementitious components, the content of sulfoaluminate cement is 36.11 wt%, silicate cement is 25 wt%, slag powder is 22.22 wt%, fly ash is 11.11 wt%, and gypsum is 5.56 wt%.

[0070] Cementitious component IV: Based on the total mass of cementitious components, the content of sulfoaluminate cement is 36.36 wt%, silicate cement is 22.73 wt%, slag powder is 22.73 wt%, fly ash is 9.09 wt%, and gypsum is 9.09 wt%.

[0071] Cementitious component V: Based on the total mass of cementitious components, the content of sulfoaluminate cement is 35wt%, silicate cement is 25wt%, slag powder is 22.5wt%, fly ash is 12.5wt%, and gypsum is 5wt%.

[0072] Fine aggregate I: The type is continuously graded quartz sand. Based on its total mass, the content of quartz sand with a particle size greater than or equal to 0.075 mm and less than 0.6 mm is 55 wt%, the content of quartz sand with a particle size greater than or equal to 0.6 mm and less than or equal to 1.18 mm is 30 wt%, and the content of quartz sand with a particle size greater than 1.18 mm and less than or equal to 4.75 mm is 15 wt%. It has been pre-wetted to a surface-dry saturated state.

[0073] Fine aggregate II: The type is continuously graded quartz sand. Based on its total mass, the content of quartz sand with a particle size greater than or equal to 0.075 mm and less than 0.6 mm is 35 wt%, the content of quartz sand with a particle size greater than or equal to 0.6 mm and less than or equal to 1.18 mm is 35 wt%, and the content of quartz sand with a particle size greater than 1.18 mm and less than or equal to 4.75 mm is 30 wt%. It has been pre-wetted to the surface dry saturation state.

[0074] Fine aggregate III: The type is discontinuously graded quartz sand. Based on its total mass, the content of quartz sand with a particle size greater than or equal to 0.075 mm and less than 0.6 mm is 40 wt%, the content of quartz sand with a particle size greater than or equal to 0.6 mm and less than or equal to 1.18 mm is 0 wt%, the content of quartz sand with a particle size greater than 1.18 mm and less than or equal to 4.75 mm is 45 wt%, and the content of quartz sand with a particle size greater than 4.75 mm and less than or equal to 9.5 mm is 15 wt%. It has been pre-wetted to a surface-dry saturated state.

[0075] Limestone: Median grain size D 50 The powder is 10μm in size and was purchased from Zhucheng Jiuqi Building Materials Co., Ltd.

[0076] Silica fume: Median particle size D 50 The powder was 0.15μm in size and was purchased from Zhucheng Jiuqi Building Materials Co., Ltd.

[0077] Hydrophobic component: Siloxane emulsion, model SILRES® BS 4004, purchased from Wacker Chemie Ltd.

[0078] Defoamer: Silicone-based defoamer, model number XIAMETER TM AFE-0700 was purchased from Dow Chemical Company.

[0079] Water-reducing agent: Polycarboxylate water-reducing agent, model Sika ViscoCrete-530P, purchased from Henan Tuotong Transportation Technology Co., Ltd.

[0080] Vinyl acetate-ethylene copolymer latex powder: model VINNAPAS® 5044N, purchased from Wacker Chemie Ltd.

[0081] Styrene-butadiene latex: Model name LIGOS TM C 3600 styrene-butadiene latex, purchased from Shengxi'ao.

[0082] In the various examples provided in this invention, all raw materials are used in parts by weight. Each part by weight is 10g. Those skilled in the art can scale up or down the production scale according to the actual preparation scale.

[0083] Example 1 S1: Mix 100 parts by weight of engineering waste soil, cementing components, ultrafine fillers, heavy metal curing agent and vinyl acetate-ethylene copolymer latex powder at 200 rpm for 90 s to carry out the first mixing, and obtain mixture I; S2: The anti-stratification viscosity modifier, water-reducing agent, defoamer and water are stirred at 500 rpm for 60 s for a second mixing to obtain mixture II; S3: Mixture I and mixture II are pre-stirred at 200 rpm for 60 s, then stirred at 800 rpm for 2 min and allowed to stand for 2 min to obtain the material after the first contact; Fine aggregate I is divided into two equal parts according to the total mass, and one part is taken each time and added to the material after the first contact in two batches. The stirring time for each batch is 45 s and the stirring speed is 500 rpm to obtain the intermediate material; S4: Add styrene-butadiene latex and hydrophobic components to the intermediate material, stir at 500 rpm for 1 min for the third mixing, let stand for 2 min, and obtain mixture III; S5: Stir the mixture III for 0.5 min, and then pour and mold the fluidized solidified soil slurry in sequence according to DBJ51-T188-2022 "Technical Standard for Engineering Application of Premixed Fluidized Solidified Soil". Cure the resulting cubic specimen with a size of 70.7 mm × 70.7 mm × 70.7 mm (curing temperature 20 ± 2℃, relative humidity ≥ 95%) to prepare fluidized solidified soil (named S-1).

[0084] Examples 2-6 This embodiment follows a similar process to Embodiment 1, except that the types and amounts of raw materials are different; and a fluidized solidified soil is prepared.

[0085] The specific types and amounts of raw materials used in Examples 1-6 are listed in Table 1.

[0086] Table 1

[0087] Comparative Example 1 This comparative example was prepared using a similar process to Example 2, except that velan gum and hydroxypropyl methylcellulose were not added, while all other steps were the same; a fluidized solidified soil (named D-1) was obtained.

[0088] Comparative Example 2 This comparative example was prepared using a similar process to Example 2, except that sodium alginate and carboxymethyl chitosan were not added, while all other steps were the same; a fluidized solidified soil (named D-2) was obtained.

[0089] Comparative Example 3 This comparative example was prepared using a similar process to Example 2, except that vinyl acetate-ethylene copolymer latex powder, styrene-butadiene latex, and hydrophobic components were not added; all other aspects were the same. A fluidized solidified soil (named D-3) was prepared.

[0090] Comparative Example 4 This comparative example follows a similar process to Example 2, except that fine aggregate I is replaced with an equal mass of fine aggregate III; a fluidized solidified soil (named D-4) is prepared.

[0091] Comparative Example 5 This comparative example was carried out using a similar process to Example 2, except that limestone and silica fume were not added; a fluidized solidified soil (named D-5) was prepared.

[0092] Comparative Example 6 This comparative example was carried out using a similar process to Example 2, except that the amount of water was increased to 58 parts by weight; a fluidized solidified soil (named D-6) was prepared.

[0093] Comparative Example 7 This comparative example was prepared using a similar process to Example 2, except that carboxymethyl chitosan was replaced with an equal mass of sodium alginate, while all other aspects remained the same; a fluidized solidified soil (named D-7) was obtained.

[0094] Comparative Example 8 This comparative example was conducted using a similar process to Example 2, except that the vinyl acetate-ethylene copolymer latex powder was replaced with an equal mass of styrene-butadiene latex, while all other aspects remained the same; a fluidized solidified soil (named D-8) was prepared.

[0095] Test Example 1 This test example is used to test the performance of the fluidized solidified soil obtained in each embodiment and comparative example. Details are as follows: Test method for bleeding rate: After the freshly mixed fluidized solidified soil slurry is thoroughly stirred, a certain mass is immediately weighed and placed into a graduated container. After leveling the surface, it is allowed to stand for 30 minutes. The mass of free water precipitated from the surface of the slurry is collected and weighed. The formula for calculating the bleeding rate is shown in Equation-I: Formula-I; in, m 泌水 This refers to the mass of free water that precipitates from the surface of the slurry after standing for 30 minutes. m 浆体 To test the initial quality of freshly mixed, fluidized solidified soil slurry.

[0096] The test method for stratification is the wet density difference method between upper and lower layers. After the freshly mixed fluidized solidified soil slurry is thoroughly stirred, it is immediately poured into a graduated cylindrical container, the surface is leveled, and it is allowed to stand for 30 minutes. After standing, the sample is divided into upper and lower layers along its height. The wet density of the upper and lower layers is measured, and the degree of stratification is characterized by the difference in wet density between the upper and lower layers. The formula for calculating the degree of stratification is shown in Equation II. Formula II; in, r 上 This is the wet density of the upper slurry after standing for 30 minutes. r 下 The wet density of the lower layer of slurry after standing for 30 minutes.

[0097] The compressive strength test method is as follows: The compressive strength test is carried out in accordance with GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)".

[0098] Test method for flexural strength: The flexural strength test shall be conducted in accordance with GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)".

[0099] Test method for water-stable performance: After casting the fluidized solidified soil slurry into specimens and standard curing to the specified age, the specimens are immersed in clean water for 7 days. They are then removed, the surface water is wiped off, and the compressive strength after immersion is tested. Simultaneously, the compressive strength of the control specimens at the same age without immersion is tested. Water-stable performance is expressed as the strength retention rate after immersion; the calculation formula for water-stable performance is shown in Equation-III. Formula-III; in, f 浸水 The compressive strength of the specimen after immersion in water for 7 days. f 未浸水 The compressive strength is that of the control specimens of the same age that were not immersed in water.

[0100] Test method for heavy metal solidification performance: After curing the fluidized solidified soil specimen to the specified age, it was crushed, cut, and sampled. Leachate was prepared according to HJ 557-2010 "Leaching Toxicity Method for Solid Waste - Horizontal Oscillation Method". The concentrations of heavy metals such as Pb, Cd, Cr, Cu, and Zn in the leachate were determined by inductively coupled plasma atomic emission spectrometry. The calculation formula for the leaching inhibition rate of heavy metals is shown in Equation-IV. Formula -IV; in, The leaching inhibition rate of heavy metals refers to the leaching inhibition rate of Pb, Cd, Cr, Cu, and Zn, respectively. The leaching concentration of solidified soil refers to the mass concentration of the corresponding heavy metal in the leachate obtained by leaching toxicity test after curing the fluidized solidified soil specimen to the specified age. The unit is mg / L. The leaching concentration of contaminated soil refers to the mass concentration of the corresponding heavy metals in the leachate obtained from contaminated engineering waste soil that has not undergone solidification treatment under the same leaching conditions, and the unit is mg / L. The formula for calculating the average leaching inhibition rate of heavy metals is shown in Equation-V: Formula -V; Among them, the five representative heavy metals are Pb, Cd, Cr, Cu, and Zn.

[0101] The fluidity test method is as follows: The fluidity test is carried out in accordance with DBJ51 / T 188-2022 "Technical Standard for Engineering Application of Premixed Flowable Solidified Soil".

[0102] The performance test results are shown in Table 2.

[0103] Table 2

[0104] Table 2 (continued)

[0105] As can be seen from the results in Table 2, Examples 1-3 have the best overall performance. Although Example 4 has lower anti-delamination ability, flexural strength and heavy metal curing rate than Examples 1-3 due to its lower content of cementitious components, ultrafine fillers and polymers, it is still significantly better than some comparative examples. The water stability performance, mechanical strength and heavy metal curing rate of Example 5 are much better than those of the comparative examples. However, due to the high content of polymers, the flowability of Example 5 is lower, so its overall performance is slightly lower than that of Examples 1-3. Example 6 uses non-optimal gradation continuous gradation fine aggregate. Although its delamination degree, bleeding rate, mechanical properties and water stability performance are worse than those of Examples 1-3, they are still significantly better than those of Comparative Example 4 which uses non-continuous gradation fine aggregate. Comparative Example 1, lacking an anti-segregation viscosity modifier, exhibited worse segregation and bleeding rate, resulting in significant differences between the upper and lower layers of the prepared fluidized solidified soil after molding. Comparative Example 2, lacking a heavy metal curing agent, showed a significantly increased heavy metal leaching concentration and a markedly reduced curing rate. Comparative Example 3, lacking a film-forming toughening agent, showed a significant decrease in flexural strength and strength retention after immersion. Comparative Example 4, using discontinuously graded fine aggregate, was most prone to problems such as sand settling, localized aggregate accumulation, and uneven distribution. Comparative Example 5, lacking ultrafine fillers, resulted in insufficient volume of the prepared fluidized solidified soil slurry, leading to reduced aggregate encapsulation capacity. The degree of stratification and bleeding rate increased; Comparative Example 6, due to its higher water consumption, achieved greater fluidity but was accompanied by more severe bleeding and segregation, and its strength decreased significantly in the later stages; Comparative Example 7, by using sodium alginate alone instead of the sodium alginate-carboxymethyl chitosan compound heavy metal curing agent, weakened the heavy metal complexation and adsorption fixation effects, and significantly reduced the average leaching inhibition rate; Comparative Example 8, by using styrene-butadiene latex alone instead of the vinyl acetate-ethylene copolymer latex powder compounded with styrene-butadiene latex as a film-forming toughening agent, reduced the uniformity of polymer distribution and the continuity of interfacial coating, and significantly reduced flexural strength and water stability.

[0106] As can be seen from the above embodiments and comparative examples, the fluidized solidified soil provided by the present invention has a high heavy metal solidification rate, good compressive strength, flexural strength and water stability, and is suitable for complex engineering scenarios with high requirements for construction fluidity, molding uniformity, environmental safety and service durability.

[0107] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A composition for fine aggregate-reinforced fluidized solidified soil, characterized in that, The composition contains engineering waste, cementitious components, fine aggregates, ultrafine fillers, heavy metal curing agents, film-forming toughening agents, anti-delamination viscosity modifiers, additives, and water. Relative to 100 parts by weight of the engineering waste soil, the content of the cementitious component is 15-45 parts by weight, the content of the fine aggregate is 10-60 parts by weight, the content of the ultrafine filler is 4-20 parts by weight, the content of the heavy metal curing agent is 0.2-2.5 parts by weight, the content of the film-forming toughening agent is 1-8 parts by weight, the content of the anti-delamination viscosity modifier is 0.01-0.2 parts by weight; the content of the additives is 0.21-3.3 parts by weight, and the content of water is 25-50 parts by weight. Based on the total mass of the cementitious components, the cementitious components contain 25-45 wt% sulfoaluminate cement, 20-35 wt% silicate cement, 10-30 wt% slag powder, 5-20 wt% fly ash and 2-10 wt% gypsum. The fine aggregate is continuously graded quartz sand, and the particle size of the quartz sand is not greater than 4.75 mm. The ultrafine filler contains limestone and silica fume; and the median particle size D of the ultrafine filler is... 50 The range is 0.05-20 μm; The heavy metal curing agent contains sodium alginate and carboxymethyl chitosan in a mass ratio of 1:0.25-3; The film-forming toughening agent contains vinyl acetate-ethylene copolymer latex powder and styrene-butadiene latex in a mass ratio of 1:0.5-0.

8.

2. The composition according to claim 1, characterized in that, Based on the total mass of the fine aggregate, the content of quartz sand with a particle size greater than or equal to 0.075 mm and less than 0.6 mm is 40-80 wt%, the content of quartz sand with a particle size greater than or equal to 0.6 mm and less than or equal to 1.18 mm is 20-60 wt%, and the content of quartz sand with a particle size greater than 1.18 mm and less than or equal to 4.75 mm is 0-25 wt%. And / or, based on the total mass of the cementitious components, the cementitious components contain 30-40 wt% sulfoaluminate cement, 20-30 wt% silicate cement, 20-25 wt% slag powder, 8-15 wt% fly ash and 4-8 wt% gypsum.

3. The composition according to claim 1 or 2, characterized in that, The anti-stratification viscosity modifier contains vesico-lamin and hydroxypropyl methylcellulose in a mass ratio of 1:0.5-1.0; And / or, the content of the anti-stratification viscosity modifier is 0.03-0.12 parts by weight; And / or, the content of the film-forming toughening agent is 2-5 parts by weight.

4. The composition according to claim 1 or 2, characterized in that, The engineering waste soil is selected from at least one of engineering waste soil and dehydrated soil from engineering waste soil, and the particle size of the engineering waste soil is not greater than 4.75 mm. The excavated soil for the project is selected from at least one of silty clay, silty soil, and dredged bottom mud.

5. The composition according to claim 1 or 2, characterized in that, In the ultrafine filler, the mass ratio of limestone to silica fume is 3-10:

1.

6. The composition according to claim 1 or 2, characterized in that, Relative to 100 parts by weight of the engineering waste soil, the additive contains 0.1-2.0 parts by weight of a water-repellent component, 0.1-1.2 parts by weight of a water-reducing agent, and 0.01-0.1 parts by weight of a defoamer.

7. The composition according to claim 6, characterized in that, The hydrophobic component is a siloxane emulsion; And / or, the water-reducing agent is selected from at least one of polycarboxylate water-reducing agents, naphthalene-based water-reducing agents, and aminosulfonate-based water-reducing agents; And / or, the defoamer is selected from at least one of silicone defoamers, polyether defoamers, and mineral oil defoamers.

8. A method for preparing fine aggregate reinforced fluidized solidified soil, characterized in that, This method is performed using any of the components in the composition according to any one of claims 1-7, comprising: S1: The engineering waste soil, cementing components, ultrafine fillers, heavy metal curing agents and vinyl acetate-ethylene copolymer latex powder are mixed in the first stage to obtain mixture I; S2: The anti-stratification viscosity modifier, water-reducing agent, defoamer and water are mixed for the second time to obtain mixture II; S3: Contact the mixture I with the mixture II and fine aggregate to obtain intermediate material; S4: The intermediate material, styrene-butadiene latex and hydrophobic component are mixed in a third mixture to obtain mixture III; S5: The mixture III is poured and molded sequentially to obtain the fluidized solidified soil.

9. Fine aggregate reinforced fluidized solidified soil prepared by the method of claim 8.

10. The application of the fine aggregate reinforced fluidized solidified soil as described in claim 9 in backfilling contaminated sites, filling underground cavities, backfilling trenches, remediation of subsidence, filling voids in underwater environments or under high groundwater conditions, and low-disturbance grouting repair of existing facilities.

Citation Information

Patent Citations

  • Solid-waste-based fluid-state solidified soil and preparation method thereof

    CN120349139A

  • Soil stabilizer based on multi-element solid waste and use method thereof

    CN121873812A